I am Ava, seeker in the snow - Stier, Catherine; Rosa, Francesca (Chicago, Illinois : Albert Whitman & Company, 2020)
After avalanche rescue dog Ava, a chocolate Labrador retriever, finally gets to help her handler, Nate, with a real rescue, she realizes that her job at the ski resort includes other important tasks, too.
Keywords: Labrador retriever -- Fiction; Working dogs -- Fiction; Ski resorts -- Fiction; Avalanches -- Fiction